Apuntes del problema de ingeniería - Domínguez Aguirre, Norberto; Paniagua Ballinas, Jorge; Rojas Ortíz, Sergio; Vega Jimenez, José (Facultad de Ingeniería, 1986)
Apuntes del problema de ingeniería
Apuntes del problema de ingeniería
Keywords: Problemas; Ingeniería